Prevalence and risk factors of sub-health and circadian rhythm disorder of cortisol, melatonin, and temperature among Chinese midwives - Chen, Xiao-Qian; Jiang, Xiu-Min; Zheng, Qing-Xiang; Wang, Hai-Wei; Xue, Heng; Pan, Yu-Qing; Liao, Yan-Ping; Gao, Xiao-Xia (Frontiers in Public Health, 2023)
Objective This study aimed to explore the influencing factors of sub-health and circadian rhythm disorder among midwives and whether circadian rhythm disorder was associated with sub-health. Methods A multi-center cross-sectional study was conducted among 91 Chinese midwives from six hospitals through cluster sampling. Data were collected by demographic questionnaire, Sub-Health Measurement Scale version 1.0, and circadian rhythm detection. Minnesota single and population mean cosine methods were used to analyze the rhythm of cortisol, melatonin, and temperature. Binary logistic regression, nomograph model, and forest plot were performed to identify variables associated with midwives' sub-health. Results There were 65 midwives with sub-health and 61, 78, and 48 midwives with non-validation of circadian rhythms of cortisol, melatonin, and temperature among 91 midwives, respectively. Midwives' sub-health was significantly related to age, duration of exercise, weekly working hours, job satisfaction, cortisol rhythm, and melatonin rhythm. Based on these six factors, the nomogram was presented with significant predictive performance for sub-health. Furthermore, cortisol rhythm was significantly associated with physical, mental, and social sub-health, whereas melatonin rhythm was significantly correlated with physical sub-health. Conclusion Sub-health and circadian rhythm disorder were generally common among midwives. Nurse administrators are supposed to pay attention and take measures to prevent sub-health and circadian rhythm disorder among midwives.